Impact of different combinations of inhaled corticosteroids and long-acting sympathicomimetics on dental health of asthmatics. - George Christoff (Journal of IMAB, 2012)
The aim of the investigation is to study the effect of inhaled corticosteroids and long-acting sympathicomimetics on dental health in asthmatics. Thirty patients, from 20 to 55 years old, participate in the study. D-, M-, F- and DMFT indexes are determined in a 6 months period. All participants fill in a questionnaire. Asthmatics complain most frequently from oral dryness, take frequently sugar and soft drinks and visit irregularly dental practitioners. A significant increase in M-index is found out at the second visit. F-index increases considerably for patients treated with Beclometasone and Formoterol and D-index decreases significantly when treated with Budesonide and Formoterol. DMFT index increases considerably for all patients. Highest values of DMFT index are registered for patients treated with Fluticasone propionate and Salmeterol. Prolonged use of inhaled drugs with greater quantities of lactose leads to more impaired dental status in asthmatics and higher values of DMFT index.